Concerns on Information System and Security Audit - Shakya, Subarna; Gupta, Abhijit (Journal of Advanced College of Engineering and Management, 2018)
Successful Information and communication technology (ICT) can cause rapid development in administrative processes. ICT strategies and ICT plans should be evaluated to align with organization visions and missions in order to achieve effective use of ICT in their organizations [1]. Efficient Software and Hardware together play a vital role giving relevant information which helps improving ways we do business, learn, communicate, entertain and work. This exposes to an environment with significant risks which are vulnerable to inside or outside attacks [2,3]. Security is a degree of protection or resistance from harm. Security can also be defined as a layer created to separate assets from threats [4]. In order to understand clearly about security, it is very important to understand important terminologies [5]. This research paper talks about important terminologies, concerns and challenges on Information System and Security Audit. This research seeks explanation from the observed phenomena, problems or behavior and thus exploratory research is used. The outcome of this research is an overview of different security concerns that must be sincerely addressed in any Information System and Security Audit. Journal of Advanced College of Engineering and Management, Vol. 2, 2016, Page:127-135